Effect of Porous Materials on Explosion Venting Overpressure and Flame of CH4/air Premixed Gas. Issue 3 (17th February 2023) - Zhuang, Chunji; Wang, Zhirong; Zhang, Yanqiong; Lu, Yawei; Zhang, Kai; Jiang, Qin; Huang, Hui; Dou, Zhan
ABSTRACT: To understand the overpressure transient and flame behavior of CH4 /air premixed gas explosion venting in the presence of porous materials, a series of explosion venting tests is conducted in a spherical vessel with a neck. The effects of pore size, porosity, thickness, and properties of porous material on Pstat, Pred, Pburst, and Pext are measured using pressure transmitters, and the image of an exploding venting jet flame passing through porous materials is captured using a high-speed camera. It is shown that the pressure wave at the high-pressure side of the explosion vent is in a critical state when the venting burst membrane ruptures without the porous materials, and the vented jet is confirmed to be under-expanded. The addition of porous materials does not significantly affect Pstat but results in the highest Pburst in porous material Al2 O3 50PPI and the highest Pred in porous material SiC 20PPI. This is consistent with the assumption that Pred > Pburst, and that an increase in Pburst corresponds to a decrease in Pred . In addition, Pext is more likely to occur at a position 250–350 mm away from the vent, and as the thickness of the porous materials increases, the possibility of an external explosion overpressure will increase. Moreover, the porous material significantly affects the venting jet flame, and as the thickness of the porous material increases, the shape of the venting jet flame resembles that of a "broom, " owing to the dynamic overpressure generated from the flame-porous material interaction.